EFFECT OF THE USE OF WOOD CHARCOAL ASH ON THE COMPRESSIVE STRENGTH OF NORMAL CONCRETE - Martin Richardo William; Kristina Sembiring; Sempurna Bangun; Pio Ranap Tua Naibaho (University Muhammadiyah Jakarta, 2023)
Wood charcoal ash is the result of chemical changes from the burning of wood. Wood charcoal contains silica which is a good binder aggregate for concrete mixtures, it is the same as the function of cement in a concrete mixture. Wood charcoal can also be used as a mixture or addition to the manufacture of reactive concrete. Concrete is a mixture of portland cement, fine aggregate, coarse aggregate and water, with or without additives that form a solid mass. Concrete is prepared from coarse aggregate and fine aggregate. Cement and water interact chemically to bind the aggregate particles into a solid mass (George Winter, 1993). Based on the results of research that has been done, the results obtained on normal concrete of 17.98 Mpa at the age of 7 days and increased at the age of 14 days of 20.73 Mpa, and 28 days of 22.94 Mpa. At the time of normal concrete mixed with wood charcoal ash 3% compressive strength of concrete again increased by 20.43 Mpa at the age of 7 days, but at the age of 14 days of concrete with a mixture of wood charcoal ash increased by 20.82 Mpa and again increased at the age of 28 days by 27.07 Mpa. The decrease continued to occur in concrete with a mixture of wood charcoal ash 8% and 13% at the age of 7 Days, 14 days, and 28 days, the increase in the compressive strength of the optimal concrete is in the concrete mixture of wood charcoal ash 3% at the age of 28 days.